STRENGTH DEVELOPMENT THROUGH HANDBALL MEANS IN THE MIDDLE SCHOOL - Petrariu Ileana (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
The purpose of this work is the finding and using an appropriate methodology through which we can influence the process of strength developing in handball. The sample of subjects consisted of students of VIIth grade from Suceava Miron Costin Secondary School. They were initially tested, according to the curriculum in terms of level of development of strength, and then followed a training program that includes specific means handball. After the final test, the results were compared and graphically represented.